Repair of giant omphalocele by component separation technique - Mutua Irene; Swaleh Shahbal (Elsevier, 2019)
Giant omphalocele management has always been a challenge because of the large fascial defect and the associated anomalies. We managed successfully a neonate with giant omphalocele and no associated anomalies by delayed repair constituting escharotic therapy initially and later managed the ventral hernia by component separation technique before her preschool years. Her recovery was non-eventful with no recurrence of the hernia on follow up. Keywords: Omphalocele, Component separation technique, Escharotic therapy